Does sorting matter for learning inequality? Evidence from East Africa - Paul Anand; Jere R. Behrman; Hai-Anh H. Dang; Sam Jones (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Inequalities in children's learning are widely recognized to arise from variations in both household- and school-related factors. While few studies have considered the role of sorting between schools and households, even fewer have quantified how much sorting contributes to educational inequalities in low- and middle-income countries. We fill this gap using data on over one million children from three countries in Eastern Africa. Applying a novel variance decomposition procedure, our results indicate that sorting of pupils across schools accounts for at least 8 per cent of the total test-score variance and that this contribution tends to be largest for children from families at either end of the socio-economic spectrum. Empirical simulations of steady-state educational inequalities reveal that policies to mitigate the consequences of sorting could substantially reduce inequalities in education.
Keywords: I24; 330; Africa; education; inequality of opportunity; sorting; variance decomposition